Strain hardening of flat samples of two–dimensional high purity Al polycrystals - Badiyan, E.E.; Tonkopryad, A.G.; Ftomov, Ye.V.; Shekhovtsov, O.V. (Вопросы атомной науки и техники, 2020)
Using the dislocation–kinetic approach based on equations describing the evolution of the average dislocation density in a material with an increase in shear strain, size effects have been theoretically studied that are associated with the effect on the strain hardening of the sample of the average grain size dₛ xsand thickness D and are caused by the dependence of the kinetic equation terms on dₛ and D. Established in a common way using the Taylor relation and experimentally confirmed the relationship between the flow stress σ and the strain degree ε was used to analyze the strain hardening of flat samples of two–dimensional high–purity Al polycrystals with different grain sizes in the range ~ 50μm < dₛ < ~ 1mm and various thicknesses in the range of ~ 50μm < Dₛ < ~ 1mm under uniaxial tension with a constant strain rate at moderate temperatures. It was shown that the dependence of the offset yield strenght σ₀.₂ on the grain size dₛ almost vanishes at dₛ > 300μm. It was found that the values of σ₀.₂ and the strain-hardening coefficient θ = dσ / dε decrease with increasing thickness D of the sample. These decreasing dependences are replaced by increasing ones with increasing degree of deformation. Stress σ and coefficient θ increase with increasing ratio D / dₛ at all stages of deformation. З використанням дислокаційно-кінетичного підходу, який ґрунтується на рівняннях, що описують еволюцію середньої густини дислокацій в матеріалі зі зростанням зсувної деформації, теоретично досліджені розмірні ефекти, які пов'язані з впливом на деформаційне зміцнення зразка середнього розміру зерен dₛ і товщини D і зумовлені залежністю членів кінетичного рівняння від dₛ і D. Встановлений прийнятим способом за допомогою співвідношення Тейлора і підтверджений експериментально зв'язок між напруженням плину σ і ступенем деформації ε використано для аналізу деформаційного зміцнення плоских зразків двовимірних полікристалів Al високої чистоти з різним розміром зерна в інтервалі ~ 50мкм < dₛ < ~ 1мм і різною товщиною в інтервалі ~ 50мкм < D < ~ 1мм при одновісному розтягуванні з постійною швидкістю деформації при помірних температурах. Знайдено, що залежність умовної границі плинності σ₀.₂ від розміру зерна dₛ практично зникає при dₛ > 300мкм. Виявлено, що значення σ₀.₂ і коефіцієнта деформаційного зміцнення θ = dσ / dε зменшуються із зростанням товщини D зразка. Ці спадні залежності перетворюються на зростаючі при збільшенні ступеня деформації. Напруження σ і коефіцієнт θ зростають зі збільшенням відношення D / dₛ на всіх етапах деформування. С использованием дислокационно-кинетического подхода, основанного на уравнениях, описывающих эволюцию средней плотности дислокаций в материале с ростом сдвиговой деформации, теоретически исследованы размерные эффекты, которые связаны с влиянием на деформационное упрочнение образца среднего размера зерен dₛ и толщины D и обусловлены зависимостью членов кинетического уравнения от dₛ и D. Установленная принятым способом с помощью соотношения Тейлора и подтвержденная экспериментально связь между напряжением течения σ и степенью деформации ε использована для анализа деформационного упрочнения плоских образцов двумерных поликристаллов Al высокой чистоты с различным размером зерна в интервале ~ 50мкм < dₛ < ~ 1мм и различной толщиной в интервале ~ 50мкм < D < ~ 1мм при одноосном растяжении с постоянной скоростью деформации при умеренных температурах. Найдено, что зависимость условного предела текучести σ₀.₂ от размера зерна dₛ практически исчезает при dₛ > 300мкм. Обнаружено, что значения σ₀.₂ и коэффициента деформационного упрочнения θ = dσ / dε убывают с ростом толщины D образца. Эти убывающие зависимости сменяются возрастающими при увеличении степени деформации. Напряжение σ и коэффициент θ возрастают с увеличением отношения D / dₛ на всех этапах деформирования.